Fabrication of Poly(vinylidene fluoride)/Multiwalled carbon nanotube nanocomposite foam via supercritical fluid carbon dioxide: Synergistic enhancement of piezoelectric and mechanical properties. (26th May 2020) - Xu, Dawei; Zhang, Huili; Pu, Lian; Li, Li
Abstract: The fabrication of poly(vinylidene fluoride) (PVDF) based foam with complicated three-dimensional (3D) geometry and excellent piezoelectric property remains great challenge worldwide. In this study, microcellular PVDF/multiwalled carbon nanotube (MWCNT) nanocomposite foaming part was fabricated by supercritical carbon dioxide (scCO2 ) bead foaming technology. With the assistance of the ball milling, the good dispersion of MWCNT particles in PVDF matrix was achieved, which promoted the heterogeneous nucleation and enhancement effects of MWCNT on PVDF, resulting in the formation of more unique and denser cells, e.g. from 3.4 × 10 5  cells/cm 3 of pure foam to 1.7 × 10 6  cells/cm 3 of the composite foam when MWCNT content was 1.5%, and high compression strength, i.e. 3.1 MPa with 1.5% MWCNT at 10% compressive strain, about 1.1 MPa higher than that of pure foam. During the bead foaming process, the induced crystallization effect of MWCNT as well as the plasticizing and squeezing effect of scCO2 on PVDF matrix contributed to the increase of the β-phase crystal in PVDF matrix, thus endowing the composite foaming part with good piezoelectric property, i.e. 6.5 V of output voltage under periodic compression, which lightened 4 LEDs and made the foaming part had wide potential application in smart electronic field.